Not So Rational Integration

Calculus Level 5

I = 0 1 ( 2 x 1 ) ln x 1 x 2 d x \large I = \int_0^1 \dfrac{(2x-1)\ln x}{1-x^2} \, dx

Find the value of the closed form of the above integral I I .
Submit your answer as 24 I \lfloor 24I \rfloor .

Notation: \lfloor \cdot \rfloor denotes the floor function .


The answer is 9.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Mark Hennings
Oct 24, 2016

We have I = 0 1 x ln x 1 x 2 d x 0 1 ln x 1 + x d x = 1 4 0 1 ln x 1 x d x 0 1 ln x 1 + x d x I \; = \; \int_0^1 \frac{x \ln x}{1-x^2}\,dx - \int_0^1 \frac{\ln x}{1+x}\,dx \; =\; \tfrac14\int_0^1 \frac{\ln x}{1-x}\,dx - \int_0^1 \frac{\ln x}{1+x}\,dx splitting the integral and applying a trivial change of variable. But 0 1 ln x 1 x d x = n = 0 0 1 x n ln x d x = n = 0 1 ( n + 1 ) 2 = ζ ( 2 ) \int_0^1 \frac{\ln x}{1-x}\,dx \; = \; \sum_{n=0}^\infty \int_0^1 x^n \ln x\,dx \; = \; -\sum_{n=0}^\infty \frac{1}{(n+1)^2} \; =\; -\zeta(2) and 0 1 ln x 1 + x x = n = 0 ( 1 ) n 0 1 x n ln x d x = n = 0 ( 1 ) n ( n + 1 ) 2 = 1 2 ζ ( 2 ) \int_0^1 \frac{\ln x}{1+x}\,x \; = \; \sum_{n=0}^\infty (-1)^n \int_0^1x^n \ln x\,dx \; = \; -\sum_{n=0}^\infty \frac{(-1)^n}{(n+1)^2} \; = \; -\tfrac12\zeta(2) (these results can be justified using the Monotonic and Dominated Convergence Theorems respectively) and hence I = 1 4 ζ ( 2 ) + 1 2 ζ ( 2 ) = 1 4 ζ ( 2 ) = 1 24 π 2 I \; = \; -\tfrac14\zeta(2) + \tfrac12\zeta(2) \; = \; \tfrac14\zeta(2) \; = \; \tfrac{1}{24}\pi^2 making the answer π 2 = 9 \lfloor \pi^2 \rfloor = \boxed{9} .

I = 1 2 0 1 ln x 2 1 x 2 d ( x 2 ) 0 1 ln x 1 x 2 d x \displaystyle I=\frac{1}{2}\int_{0}^{1}\frac{\ln x^2}{1-x^2}d(x^2)-\int_{0}^{1}\frac{\ln x}{1-x^2}dx

Now, I) 0 1 x a ln b x d x = ( b ) a ( b ) ( 0 1 x a d x ) = ( b ) a ( b ) ( 1 a + 1 ) = ( 1 ) b b ! ( a + 1 ) b + 1 \displaystyle \text{I) } \int_{0}^{1}x^a \ln^b x dx =\frac{\partial^{(b)}}{\partial a^{(b)}} (\int_{0}^{1}x^a dx) = \frac{\partial^{(b)}}{\partial a^{(b)}} (\frac{1}{a+1})= \frac{(-1)^b b!}{(a+1)^{b+1}}

II) F ( m ) = 0 1 ln m ( x ) 1 x d x = n = 0 0 1 x n ln m ( x ) d x = n = 0 ( 1 ) m Γ ( m + 1 ) ( n + 1 ) m + 1 = ( 1 ) m Γ ( m + 1 ) ζ ( m + 1 ) \displaystyle \text{II) } F(m)=\int_{0}^{1} \frac{\ln^m( x)}{1-x}dx =\sum_{n=0}^{\infty} \int_{0}^{1} x^n \ln^m (x) dx = \sum_{n=0}^{\infty} \frac{(-1)^m\Gamma(m+1)}{(n+1)^{m+1}} = (-1)^m\Gamma(m+1)\zeta(m+1)

I = 1 2 0 1 ln y 1 y Set x 2 = y n = 0 0 1 x 2 n ln x d x \displaystyle I = \underbrace{\frac{1}{2}\int_{0}^{1} \frac{\ln y}{1-y}}_{\text{Set }x^2=y} - \sum_{n=0}^{\infty} \int_{0}^{1} x^{2n}\ln x dx

Using I & II \text{I \& II } , I = 1 2 F ( 1 ) + n = 0 1 ( 2 n + 1 ) 2 = 1 2 ζ ( 2 ) + π 2 8 = π 2 24 \displaystyle I = \frac{1}{2}F(1) +\color{#D61F06}{\sum_{n=0}^{\infty} \frac{1}{(2n+1)^2}} = \color{#333333}{-\frac{1}{2}\zeta(2)+\frac{\pi^2}{8}=\frac{\pi^2}{24}}

Thus the answer is π 2 = 9 \displaystyle \lfloor{\pi^2\rfloor} = \boxed{9}

Note : \text{Note :} The R e d \color{#D61F06}{Red} sum can be evaluated in various ways, the below is using integration :

If we define G ( s ) = n 0 1 ( 2 n + 1 ) s \displaystyle G(s)=\sum_{n\ge 0}\frac{1}{(2n+1)^s} then we can easily see that G ( s ) = ( 1 2 s ) ζ ( s ) G(s)=(1-2^{-s})\zeta(s) so that ζ ( 2 ) = 4 3 G ( 2 ) \displaystyle \zeta(2)=\frac{4}{3}G(2) , so computing G ( 2 ) \displaystyle G(2) will give us ζ ( 2 ) \zeta(2) also.

G ( 2 ) = n = 0 1 ( 2 n + 1 ) 2 = n = 0 1 2 n + 1 1 2 n + 1 = 0 1 0 1 n = 0 ( x y ) 2 n d x d y = 0 1 0 1 d x d y 1 x 2 y 2 \displaystyle G(2)=\sum_{n=0}^{\infty}\frac{1}{(2n+1)^2} =\sum_{n=0}^{\infty}\frac{1}{2n+1}\frac{1}{2n+1}=\int_{0}^{1}\int_{0}^{1}\sum_{n=0}^{\infty}(xy)^{2n}dx dy= \int_{0}^{1}\int_{0}^{1} \frac{dxdy}{1-x^2 y^2}

1 2 ( 0 1 0 1 d x d y 1 + x y + d x d y 1 x y ) = 1 2 ( 0 1 ln ( 1 + y ) y d y 0 1 ln ( 1 y ) y d y ) = 1 2 ( π 2 12 + π 2 6 ) = π 2 8 \displaystyle \frac{1}{2}(\int_{0}^{1}\int_{0}^{1} \frac{dxdy}{1+xy}+\frac{dxdy}{1-xy})=\frac{1}{2}(\int_{0}^{1}\frac{\ln(1+y)}{y}dy-\int_{0}^{1}\frac{\ln(1-y)}{y}dy) = \frac{1}{2}(\frac{\pi^2}{12}+\frac{\pi^2}{6}) = \frac{\pi^2}{8}

Thus ζ ( 2 ) = 4 3 G ( 2 ) = π 2 6 \displaystyle \zeta(2)=\frac{4}{3}G(2)=\frac{\pi^2}{6}

Actually, if you already know and use ζ ( 2 ) \zeta (2) , you can calculate the reciprocal of odd squares very easily.

Hint: Integers = Odd integers + Even integers.

Calvin Lin Staff - 4 years, 7 months ago

Log in to reply

Thanks for having a look ! . I know that part , n 0 1 ( 2 n + 1 ) s = ( 1 2 s ) ζ ( s ) \displaystyle \sum_{n\ge 0}\frac{1}{(2n+1)^s} = (1-2^{-s})\zeta(s) for s > 1 s>1

Aditya Narayan Sharma - 4 years, 7 months ago

Log in to reply

Right, so if you're already using ζ ( 2 ) \zeta (2) in the solution, it seems counter-intuitive to extensively prove this summation. It would make more sense to prove ζ ( 2 ) = π 2 6 \zeta (2) = \frac{ \pi^2}{6} using the approach first, and then explain how to get the odd squares.

Calvin Lin Staff - 4 years, 7 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...